Maslak al-Sālikīn Ilā Ḥaḍrat Rabb al-‘Ālamīn: Potret Tafsir dalam Naskah Tasawuf di Kalimantan Selatan Periode Modern - Ahmad Mujahid (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2015)
This article is a response to the lack of research on the Quranic exegesis in the early development of Islam in the archipelago. This article examines the exegetical aspects in Maslak al-Sālikīn Ilā Ḥaḍrat Rabb al-‘Ālamīn, a Jawi manuscript from Negara, South Kalimantan. This text contains quotations from verses from the Quran translated into the Malay language, so the text is considered to have an important role in translating Islam to the local context. This kind of translation method is tarjamah tafsīrīyah, ie copying or transferring sentences from the original language into another language without having to depend on the structure and composition of the original language so the method is more concerned with the content of the message contained in the target language. On this basis, this text can be considered as one of the important references Quranic exegesis studies in the past. — Artikel ini merupakan jawaban atas kelangkaan kajian tafsir Alquran pada masa awal perkembangan Islam di Nusantara. Objek kajian artikel ini adalah aspek tafsir dalam teks Maslak al-Sālikīn Ilā Ḥaḍrat Rabb al-‘Ālamīn, sebuah teks dari daerah Negara, Kalimantan Selatan, yang beraksara Jawi, berbahasa Melayu. Teks ini berisi kutipan dari ayat-ayat Alquran yang diterjemahkan ke dalam bahasa Melayu sehingga teks ini dianggap memiliki peran penting dalam hal penerjemahan Islam ke dalam konteks lokal. Metode penerjemahan semacam ini merupakan tarjamah tafsīrīyah, yaitu menyalin atau mengalihkan kalimat dari bahasa asal ke dalam bahasa yang lain tanpa bergantung dengan struktur dan susunan bahasa asal sehingga metode ini lebih mementingkan isi pesan yang terdapat di dalam bahasa sasaran. Atas dasar itulah teks ini dapat dipandang sebagai salah satu kajian tafsir yang penting di masa lalu.